2021
DOI: 10.1016/j.cmi.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus transmission via breast milk in suckling mice

Abstract: Objectives: Infectious Zika viral particles were detected in human milk; however, whether they can be transmitted via breastfeeding remains unknown, so our objective was to clarify this.Methods: Here, in a natural breastfeeding model, wild-type (C57Bl/6; WT) or interferon a/b (IFNa/b) receptor-deficient (A129; KO) murine dams on day 1 post-delivery were infected with Zika virus (ZIKV) intraperitoneally, and the neonates were suckled. In a novel artificial feeding model, WT suckling mice at 1 day old were fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Although the exact nature of ZIKV in breast milk remains unknown, either cell-free, cell-associated, or as extracellular vesicle-cloaked virus clusters, breast milk of some infected mothers was shown to be infectious (Dupont-Rouzeyrol et al, 2016;Blohm et al, 2017;Cavalcanti et al, 2017;Sotelo et al, 2017). Several studies demonstrated that ZIKV viral particles remained infectious in fresh breast milk (Pfaender et al, 2017;Conzelmann et al, 2019) and that potential antiviral properties of breast milk were not sufficient to prevent ZIKV transmission to mice neonates (Pang et al, 2020). These observations led us wonder whether ZIKV could orally infect a suckling child during breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact nature of ZIKV in breast milk remains unknown, either cell-free, cell-associated, or as extracellular vesicle-cloaked virus clusters, breast milk of some infected mothers was shown to be infectious (Dupont-Rouzeyrol et al, 2016;Blohm et al, 2017;Cavalcanti et al, 2017;Sotelo et al, 2017). Several studies demonstrated that ZIKV viral particles remained infectious in fresh breast milk (Pfaender et al, 2017;Conzelmann et al, 2019) and that potential antiviral properties of breast milk were not sufficient to prevent ZIKV transmission to mice neonates (Pang et al, 2020). These observations led us wonder whether ZIKV could orally infect a suckling child during breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…By exposing lactating dams to a Brazilian strain of ZIKV 3 days after parturition, we noted that 39% of suckling pups became infected. Interestingly, MTCT of another strain of ZIKV (Asian strain) by breastfeeding was recently highlighted (Pang et al, 2020). Because ZIKV had been previously demonstrated to be excreted in murine breast milk, transfer of infectious particles from ZIKV-infected dams to suckling pups via oral swallowing of contaminated breast milk is thus very probable.…”
Section: Discussionmentioning
confidence: 99%
“…While the antiviral activity of HM and its components against numerous viral pathogens have been described in literature, its role in protecting against emerging arboviruses has been poorly PLOS NEGLECTED TROPICAL DISEASES investigated so far [25,58,59]. In this study we addressed this issue focusing on two emerging flaviviruses: we assessed the anti-ZIKV and the anti-USUV activity of human milk in its different stages of maturation and we explored the antiviral contribution of specific components, namely the HM-EVs and the HM-GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study reporting the intrinsic anti-USUV activity of human milk. On the contrary, Pang et al recently indicated a potential anti-ZIKV action of HM in an artificial feeding model mouse [ 25 ] and other two reports demonstrated that breast milk is able to inactivate ZIKV in a time-dependent manner. These latter studies attributed the antiviral potential to the fat containing cream fraction of human milk, in which the free fatty acids, released upon storage by milk lipases in a time-dependent manner, incorporate into the viral envelope thereby destroying the viral particle [ 30 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation